Non-linear relationship between the dietary inflammatory index and stroke risk in metabolically healthy obese individuals: an analysis of NHANES 1999-2023 data - Zhao, Chuanwei; Yang, Yane; Yang, Yunjie; Yang, Wenzhou; Mu, Lin; Jia, Yan (Frontiers in Nutrition, 2025)
BackgroundStudies on the relationship between the dietary inflammatory index (DII) and stroke risk in metabolically healthy obese (MHO) individuals are limited. This study aimed to explore the association between DII and stroke risk in MHO individuals, using data from the National Health and Nutrition Examination Survey (NHANES) 1999-2023.MethodsWe performed a cross-sectional analysis of the NHANES, including 9872 MHO adults—defined as having a body mass index (BMI) ≥ 30 kg/m2 and no more than three metabolic abnormalities. Dietary intake was collected through 24-h recalls and weighted by the corresponding inflammatory effect coefficients, the sum of these weighted values yielded each participant’s DII score. Stroke status was ascertained from self-reported physician diagnosis recorded in the same survey cycle. Survey-weighted logistic regression and restricted cubic splines evaluated the DII–stroke association, while model performance was quantified with the area under the receiver operating characteristic (ROC) curve and decision-curve analysis (DCA).ResultsA significant non-linear relationship was observed between DII and stroke risk. Below a DII score of 2.0, each 1-unit increase in DII was associated with a 32% higher stroke risk (OR: 1.32, 95% CI: 1.04–1.66; p = 0.02). Above this threshold, each 1-unit increase in DII was associated with a 38% reduction in stroke risk (OR: 0.62, 95% CI: 0.44–0.89; p = 0.01). The model’s predictive performance showed an AUC of 0.801 for the fully adjusted model.ConclusionThis study demonstrated a non-linear relationship between DII and stroke risk in MHO individuals, with a threshold effect at DII = 2.0. The DII may serve as a valuable predictor of stroke risk and guide dietary interventions in this population.